2023
DOI: 10.3390/jrfm16040224
|View full text |Cite
|
Sign up to set email alerts
|

Investment Efficiency and Earnings Quality: European Evidence

Abstract: This study aims to analyze the relationship between earnings quality and investment efficiency in the European context, in order to understand whether higher earnings quality mitigates investment inefficiencies. To further understand the relationship between earnings quality and investment efficiency, the roles of cash and financial constraints are also analyzed. We use firm-year data based on unbalanced panel data, and control for country, year, and industry fixed effects using a sample composed of listed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
4
1
1
Order By: Relevance
“…While in Model 1 the DAC variable is not statistically significant, in Model 2 it is significant at a 5% level, exhibiting a positive sign, suggesting that when discretionary accruals increase, this enhances overinvestment, and this in turn means that overinvesting tends to increase for firms that have a lower accounting information system quality in accordance to Gaio et al (2023), Yuan et al (2022), Lei et al (2022), Cardoso (2019), Linhares et al (2018), andBiddle et al (2009). Model 2 allows us to support our H2.…”
Section: Econometric Results and Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…While in Model 1 the DAC variable is not statistically significant, in Model 2 it is significant at a 5% level, exhibiting a positive sign, suggesting that when discretionary accruals increase, this enhances overinvestment, and this in turn means that overinvesting tends to increase for firms that have a lower accounting information system quality in accordance to Gaio et al (2023), Yuan et al (2022), Lei et al (2022), Cardoso (2019), Linhares et al (2018), andBiddle et al (2009). Model 2 allows us to support our H2.…”
Section: Econometric Results and Discussionmentioning
confidence: 58%
“…In that sense, firms with a low accounting information system quality would have difficulties obtaining additional funds to support the investment projects. In the same vein, Gaio et al (2023) find empirical evidence that a higher earnings quality mitigates investment inefficiencies, both underinvestment and overinvestment. However, the findings of Rahman et al (2013) suggest that earnings management among underinvesting firms reduces information asymmetry.…”
Section: Role Of Accounting Information System On Investment Efficiencymentioning
confidence: 86%
See 1 more Smart Citation
“…Nissim (2022) conducted a comprehensive analysis of earnings quality issues, linking financial statement indicators to specific concerns using a working definition of earnings quality. Gaio (2023) demonstrated a positive correlation between investment efficiency and earnings quality, suggesting higher earnings quality reduces investment inefficiencies. Yahay et al (2017) revealed firm size affects earnings quality in Nigeria's listed deposit money banks, and integrated revenue-raising strategies have a significant positive impact on earnings quality.…”
Section: Introductionmentioning
confidence: 94%
“…‫أل‬ ‫فس‬ ‫لرولهد‬ ‫ةع‬ ‫لر‬ ‫كلهدممسقاس‬ ‫ر‬ ‫حل‬ ‫ل‬ ‫لدألاف‬ ‫لهدم.تثمه‬ ‫ه‬ ‫رال‬ ‫تييحل‬ ‫عهألهدم‬ ‫نلق‬ ‫فولت‬ ‫تعالا‬ Muchtar et al, 2018 (Sapuan et al, 2021;Sinaga and Maksum, 2022;Yousef and Ojah, 2022) ‫.تمهل‬ ‫جلقآلهألرهلاللجل‬ ‫حل‬ ‫هلر‬ ‫ثلق‬ ‫لهلرعسةحلم‬ ‫ا‬ ‫رول‬ ‫هلهدمضهاأل‬ ‫لر‬ ‫آلهدممسقاس‬ ‫حلر‬ ‫م‬ ‫هدم.س‬ ‫يل‬ ‫لهلبهق‬ ‫ل‬ ‫سد‬ ‫لهدم‬ ‫لرةسق‬ ‫ل‬ ‫هاس‬ ‫لهدلق‬ ‫ةض‬ ‫لرهل‬ ‫سلرسلق‬ ‫ةهمتفسلهد.سةهأحل‬ ‫تييل‬ ‫عهألهدم‬ ‫نلق‬ ‫لت‬ ‫ز‬ ‫نس‬ ‫يلاللرباهلا‬ ‫لافالهلبهق‬ ‫قهمألر‬ ‫د‬ ‫الأل‬ ‫هد.س‬ (Chung et al, 2005;Abughniem et al, 2020;Lai et al, 2020) (Biddle and Hilary, 2006;Biddle et al, 2009;Rad et al, 2016;Eissa et al, 2023 (Chung et al, 2005;Abughniem et al, 2020;Lai et al, 2020) ‫ل‬ ‫و‬ ‫عس‬ ‫ل‬ ‫ه‬ ‫لريا‬ ‫مسب‬ ‫ل‬ ‫ن‬ ‫لت‬ ‫لهأللهن‬ ‫هاس‬ ‫لهدلق‬ ‫لر‬ ‫لهدةليل‬ ‫ل‬ ‫لق‬ ‫مس‬ ‫ل‬ ‫ح‬ (Gaio and Raposo, 2011;Hau, 2017;Bukit et al, 2019 Brush et al, 2000;Chung et al, 2005;Hau, 2017;Butt et al, (Chen et al, 2012;Tang et al, 2014;Sapuan et al, 2021) Zhou and Ruland, 2006;Huang et al, 2009) . ‫لل‬ ‫ل‬ ‫ل‬ ‫تلرالس‬ ‫األهدسكسدألد‬ ‫لر‬ ‫مهألمسبيلهلاتعالسةلهدمعسافولرولهدعللر‬ ‫نلق‬ ‫لت‬ ‫هاس‬ ‫ةضلهدلق‬ ‫كسدكلربكلل‬ ‫ل‬ ‫لهلاتثمسق‬ ‫لرهط‬ ‫لرمسقاس‬ ‫لر‬ ‫لهدعل‬ ‫و‬ ‫لل‬ ‫لر‬ ‫يح‬ ‫لهدعه‬ ‫أ‬ ‫الل‬ ‫هد‬ (Wang et al, 2015;Gaio et al, 2023;Eissa et al,…”
Section: ‫البحث‬ ‫ملخص‬unclassified